Effective demand, exogenous normal utilization and endogenous capacity in the long run. Evidence from a CVAR analysis for the US - Christian Schoder (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2012)
Using the Cointegrated VAR framework, we provide evidence for the US manufacturing sector that the principle of effective demand in a growth context, by which a permanent demand shock has a permanent growth effect, is consistent with the stylized fact of a stationary rate of capacity utilization, since production capacities adjust endogenously to current output.
urn:nbn:de:101:1-2013031310800
Keywords: E12; E22; C22; 330; effective demand; stationary utilization rate; endogenous capacity; cointegrated vector autoregression